PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.5 SMP NEGERI 4 PEKANBARU - M. Sergio Virnando Virnando; Syofni '; Kartini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is classroom action research that aims to improve learning process andto increase mathematics achievementwith appliedthe learning model of Problem Based Learning. The subject of this research is student of class VIII.2SMPN 4Pekanbaru in the secondsemester academic years 2014/2015, which amounted to34students, consist of 13 boys and 21 girls. The research consisit of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection.At the end of every cycle the quiz will be implemented. Data collectionis done by observation and tests in the form of quiz. The result of research shows that implementation of learning process on cycle I and II had happened improvement from before the action research. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Most of students were very confidenced  and actived in learning process,such as while they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning.Number of students that reach Minimum Mastery Criteriaincrease from basic score toquiz I and II. The number percentage of students who reach Minimum Mastery Criteria on basic, quiz I and daily test II  are respectively 67,65%, 79,41% and 79,41%.Results of this research indicates that appication of the learning model of Problem Based Learningcan improve learning process and increase mathematics achievementfrom the students at class VIII.2 SMPN 4 Pekanbaru in the second semester academic years2014/2015. Key Words: Mathematics Achievement, Problem Based Learning, Class ActionResearch